NON-COMMUNICABLE DISEASES RISK FACTORS AND THEIR CONTRIBUTION TO NCD INCIDENCES IN KENYA - Mwai, Daniel; Muriithi, Moses (European Scientific Journal, ESJ, 2015)
Although mortality from communicable diseases and poor nutrition have been declining, non-communicable diseases have been on the rise in developing countries. Consequently, this poses a serious challenge to health programming. There are predictions that NCDs will continue to rise in the coming years resulting to at least 9 million deaths every year. This death rate would occur among people who are below 60 years of age in sub-Saharan Africa. NCDs are associated with some underlying risk factors of which most of them can be tackled through clear policy intervention. Notably, many risk factors are also known to be country specific which requires country specific studies. The efforts towards the prevention of NCDs in Kenya are inadequate. This could be attributed to inadequate understanding of the contribution of suspected risk factors to NCDs. In addition, addressing the risk factors associated with these diseases may present a cheaper and long-term solution to the problem of rising cases of NCDs in Kenya. This paper uses household national survey data to estimate the influence of risk factors associated with NCD in Kenya. A probit binary model was used while controlling the econometric problem associated with endogeniety and heterogeneity assumptions. The key finding is that income, distance, peer, effects on area of residence, and education are key risk factors associated with the rising NCD in Kenya. Age and gender are non-policy variables that increased the likelihood of one getting a NCD. This study has pointed out that the health care system in Kenya needs to develop mechanisms for promoting preventive care for NCDs. Also, effective prevention methods that address the NCD risk factors are preferable for treatment. However, these prevention methods are not only expensive, but are also protracted.